2016
DOI: 10.1146/annurev-resource-100815-095459
|View full text |Cite
|
Sign up to set email alerts
|

Contract Farming in Developed and Developing Countries

Abstract: Contract farming (CF) has long been practiced but is becoming increasingly common in both developed and developing countries with the heightened interest of consumers in food safety and quality. Under CF, farmers and buyers make advance agreements on volume, quality, time of delivery, use of inputs, and price or pricing formula. This article critically reviews the literature on CF to assess how it contributes to improving production efficiency and income of farmers in general and of small-scale farmers in part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
173
2
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 195 publications
(192 citation statements)
references
References 132 publications
13
173
2
4
Order By: Relevance
“…Our findings agree with those of Prowse (2012), Wang et al (2014b), Minot and Ronchi (2015), and Otsuka et al (2016). Oya (2012) does not mention the role of previous collective marketing experience, though he does emphasise the importance of collective action for the negotiation capacities of farmers when contracting with the firm.…”
Section: Agreements and Disagreements With Other Studies Or Reviewssupporting
confidence: 90%
See 4 more Smart Citations
“…Our findings agree with those of Prowse (2012), Wang et al (2014b), Minot and Ronchi (2015), and Otsuka et al (2016). Oya (2012) does not mention the role of previous collective marketing experience, though he does emphasise the importance of collective action for the negotiation capacities of farmers when contracting with the firm.…”
Section: Agreements and Disagreements With Other Studies Or Reviewssupporting
confidence: 90%
“…In our conclusion that participation in contract farming tends to be biased towards the better-off farmers, we coincide with Wang et al (2014b), Prowse (2012:85), and Otsuka, Nakano and Takahashi (2016). These reviews found that although most contract farming schemes target and include small farms, most included farms are larger.…”
Section: Agreements and Disagreements With Other Studies Or Reviewssupporting
confidence: 68%
See 3 more Smart Citations